Nato and the Transatlantic Alliance in the Twenty-First Century - Williams, G. author. aut Link
XIV, 250 p.
Keywords: This book examines the nature of international politics in the twentieth century. It encapsulates those essential and enduring features likely to be present in the twenty-first century. One important feature is the friction generated by nation states attempting to coexist in a still largely unequal and hierarchical system of states. The possible impact of three powerful, simultaneous and intersecting revolutions on international relations and the future of NATO is assessed in relation to the twenty-first century.